Implied Trusts And Illegality: How Clean is Clean? - Bulan, Ramy (Journal of Malaysian and Comparative Law, 2019)
"He who comes to equity must come with clean hands" The maxim that a plaintiff in equity must approach the court with clean hands alludes to a number of distinct rules whereby a particular conduct may lead to a refusal of relief. This maxim is closely linked with "he who seeks equity must do equity". It draws attention to the origins of equity in a "court of conscience" and serves to point to a very important distinction between law and equity, viz, the ability of equity to give conditional relief.